FLORA AND VEGETATION OF COASTAL WETLANDS OF THE COPIAPÓ RIVER, ATACAMA, CHILE AND THE IMPACT OF THE 2015 FLOOD FLORA Y VEGETACIÓN DE HUMEDALES COSTEROS EN EL RÍO COPIAPÓ, ATACAMA, CHILE Y EL IMPACTO DEL ALUVIÓN DE 2015 - Ramírez, None; Westermeier, Renato; Fariña, José Miguel; Martín, Cristina San; Vidal Ojeda, Osvaldo Javier; Vidal, Osvaldo; Ojeda, Nelson; Pérez, Yéssica; Morales, Manuel (My University, 2022)
The flora, vegetation and the effect on the first from the March 2015 flood on two coastal wetlands (Las Salinas and Copiapó river mouth) located in the Atacama Region of Chile. The flora consisted of 21 species from a phytosociological table of 88 vegetation samples, 11 species collected outside the samples and 11 that appeared after the 2015 flood, giving in total 44 species. In the biological spectrum, phanerophytes, camephytes and hemicryptophytes dominated. Four plant formations were distinguished: submerged acuatic plants, swamp with large helophytes, marshes and forests. Ten plant associations were determined: 2 submerged Ruppietum maritimae and Charetum- asoc. nova prov., 3 swamps with large helophytes Typhaetum angustifoliae, Phragmitetum australis, Schoenoplectetum californiae, 5 from marshes Schoenoplectetum americanae, Chorizantho-Sarcocornietum neeii asoc. nova, Tessario-Distichletum spicatae asoc. nova, Tessario-Juncetum acutae asoc. nova and 1 forest Geoffreetum decorticans asoc. nova. New associations are described, adding phytosociological tables and a type vegetation sample is designated for each one. These results are discussed and the flora is compared with that of 5 other coastal wetlands in the Norte Grande of Chile, demonstrating the lack of basic studies of flora and vegetation in them.
Keywords: big north; chile; coastal wetlands; desert; flood; vegetation